A catalyst for synthesizing polyethylene oxide and a preparation method thereof
By using fructooligosaccharide-modified ZIF-8 loaded calcium ammonium catalyst, the problem of difficulty in controlling the molecular weight and molecular weight distribution of the catalyst in the synthesis of polyethylene oxide is solved, achieving high yield, high purity, concentrated molecular weight distribution, and good thermal stability. Polyethylene oxide synthesis effect.
Patent Information
- Application Number
- CN202411259227.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-10
AI Technical Summary
It is difficult for existing catalysts to accurately control the molecular weight and molecular weight distribution during the polyethylene oxide synthesis process, resulting in low product properties and purity and insufficient stability of the catalyst.
ZIF-8 modified with fructo-oligosaccharides is used to load the calcium ammonia catalyst. The dispersion and stability of the calcium ammonia catalyst are improved by modifying the pores and surface properties of ZIF-8. The catalyst is loaded under low temperature and low speed stirring conditions to control the loading quality. ratio to prevent overloading.
It has achieved high yield, high purity and concentrated molecular weight distribution of polyethylene oxide, and has good thermal stability. It has greatly improved the quality of low molecular weight polyethylene oxide, making its purity reach more than 99.70wt%, with a median molecular weight of 350,000 to 65 Between ten thousand.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material synthesis, and in particular relates to a catalyst for synthesizing polyethylene oxide and a preparation method thereof. Background Art
[0002] Polyethylene oxide (PEO) is a widely used polymer material. For example, in medicine, polyethylene oxide can be used as a thickener, stabilizer and adhesive for the manufacture of tablets, capsules and suspensions, etc. It can also be used to prepare controlled-release drug carriers. In cosmetics, polyethylene oxide can be used as an emulsifier, thickener and moisturizer. In the papermaking industry, polyethylene oxide can be used for surface sizing and reinforcing agents for paper. In water treatment, polyethylene oxide can be used as a flocculant and can also be used to prepare reverse osmosis membranes and ultrafiltration membranes. In building materials, polyethylene oxide can be used as an admixture for cement and concrete to improve its fluidity and crack resistance.
[0003] Polyethylene oxide is mainly synthesized through the ring-opening polymerization of ethylene oxide. During the polymerization process, ethylene oxide undergoes a ring-opening reaction under the action of a catalyst to form polyethylene oxide chains. The polymerization reaction can be carried out in different systems such as bulk, solution or suspension. The synthesis of polyethylene oxide usually requires the use of metal catalysts. Catalysts play a vital role in the synthesis of polyethylene oxide. They can reduce the activation energy of the polymerization reaction, increase the reaction rate, and control the molecular weight and molecular weight distribution of the polymer. In addition, catalysts can also affect the structure and properties of the polymer, such as crystallinity, solubility and thermal stability.
[0004] With the continuous research and development of polyethylene oxide synthesis technology, catalysts are also constantly improved and innovated. Early catalysts were mainly alkali metals and their oxides. Although these catalysts can promote the polymerization reaction, due to the fast reaction rate, they will lead to a wide molecular weight distribution and it is difficult to control the precise molecular weight of the product. Later, people developed catalysts such as alkaline earth metals and their oxides and hydroxides. The activity of alkaline earth metal catalysts is relatively moderate. To a certain extent, they can better control the polymerization reaction rate, which is conducive to obtaining polyethylene oxide products with a relatively narrow molecular weight distribution.
[0005] Generally speaking, the polymerization rate increases with the increase in the amount of catalyst. However, excessive catalyst will trigger side reactions, resulting in a decrease in the molecular weight of the product and a broadening of the molecular weight distribution. If the amount of catalyst is too small, the polymerization rate is slow and the product of the desired molecular weight cannot be obtained within a reasonable time.
[0006] In addition, reaction temperature, pressure and other conditions will also affect the polymerization reaction. Higher reaction temperature will enhance the activity of the catalyst and accelerate the polymerization reaction, but it will also lead to a decrease in the molecular weight of the product because side reactions such as chain transfer are more likely to occur at high temperatures. Appropriate reaction pressure can promote the ring-opening polymerization of ethylene oxide, but if the pressure is too high or too low, it will also affect the activity of the catalyst and the molecular weight of the product.
[0007] Therefore, it is very important to select suitable catalyst and dosage, and control reaction conditions, for obtaining the product of desired molecular weight in the preparation of polyoxyethylene by ring-opening polymerization of ethylene oxide. Especially the selection of catalyst directly affects the property and purity of polyoxyethylene product. At present, catalyst has improved various composite catalysts, mainly including calcium and strontium bimetallic catalyst system, ammonia calcium nano-silicon dioxide catalyst system, ammonia calcium diethyl zinc solution composite catalyst system, etc. Except composite catalyst, adopt modifier to modify catalyst, also can further improve catalyst activity, better control reaction system, obtain molecular weight distribution relatively concentrated, purity relatively high polyoxyethylene product. For example, propylene oxide and acetonitrile are to the activity modification of ammonia calcium catalyst, but also can not meet the use requirement of higher product purity and molecular weight distribution concentration.
[0008] With the continuous development and progress of science and technology and the requirements for high-quality development, various application fields have increasingly higher requirements for the properties and purity of polyethylene oxide. Therefore, it is necessary to continuously develop and improve catalyst performance and the preparation process of polyethylene oxide to meet the increasingly high usage needs. Summary of the invention
[0009] In order to further control the activity of the catalyst, improve the stability in use, obtain polyethylene oxide with a precise target molecular weight, and obtain polyethylene oxide with a more concentrated molecular weight distribution and higher purity. The present invention provides a catalyst for synthesizing polyethylene oxide and a preparation method thereof. The ammonia calcium catalyst is loaded with ZIF-8 modified with oligofructose to improve the dispersibility and stability of the ammonia calcium catalyst, and methacrylonitrile is used to modify the ammonia calcium catalyst. The catalyst catalyzes ethylene oxide to prepare polyethylene oxide with high yield and high purity, and the molecular weight distribution is very concentrated, and the thermal stability is good, which greatly improves the quality of low molecular weight polyethylene oxide. The specific technical scheme is as follows:
[0010] A catalyst for synthesizing polyethylene oxide, wherein the catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, and the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = (25-30): (5-8); the modified ZIF-8 is oligofructose-modified ZIF-8.
[0011] Among the above catalysts, ZIF-8 is a metal organic framework material ZIF-8 with a high specific surface area, a particle size of more than 650nm, and a specific surface area of more than 1500m² / g.
[0012] Among the above catalysts, the preparation method of the calcium ammonia catalyst comprises the following steps:
[0013] S1: According to the mass ratio of liquid ammonia:metal calcium = (80-100): (1-1.5), liquid ammonia and metal calcium are subjected to complex reaction under the protection of inert gas to generate ammonia-calcium complex liquid;
[0014] S2: According to the mass ratio, calcium ammonia complex solution: modifier: solvent = (80-100): (0.3-1): (100-150), dissolving the modifier in the solvent, and then adding the calcium ammonia complex solution to carry out modification reaction, deamination, aging, and obtaining a crude calcium ammonia catalyst;
[0015] S3: The crude product of the calcium ammonia catalyst is resuspended, washed and filtered 2 to 4 times with a solvent, and finally filtered to obtain a solid and dry it to obtain the calcium ammonia catalyst.
[0016] In the preparation method of the above-mentioned calcium ammonia catalyst, in S1, the purity of metallic calcium is above 99.5%; the temperature of the complex reaction is -50°C to -35°C, and the time of the complex reaction is 1h to 1.5h.
[0017] In the preparation method of the calcium ammonia catalyst, in S2, the mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = (5-10): (0.5-1): (0.3-0.6);
[0018] In the preparation method of the above-mentioned calcium ammonia catalyst, in S2, the mass ratio of the solvent components is: No. 120 solvent oil: toluene = (8-10): (1.5-3).
[0019] In the preparation method of the above-mentioned calcium ammonia catalyst, in S2, the temperature of the modification reaction is -35°C to -34°C, and the time of the modification reaction is 1.5h to 2h; the temperature of the deamination is -10°C to 20°C, and the time of the deamination is 2h to 3h; the temperature of the aging is 130°C to 150°C, and the aging time is 2h to 3h.
[0020] In the above-mentioned method for preparing the calcium ammonia catalyst, in S3, the drying temperature is above 120°C.
[0021] The above-mentioned method for preparing a catalyst for synthesizing polyethylene oxide comprises the following steps:
[0022] N1: According to the mass ratio, oligofructose: ZIF-8: purified water = (5-8): (50-60): (250-300), first dissolve oligofructose in purified water, then add ZIF-8, mix by ultrasonication, separate by centrifugation, take the solid, and vacuum dry to obtain modified ZIF-8;
[0023] N2: According to the mass ratio, calcium ammonia catalyst: modified ZIF-8: purified water = (5-8): (25-30): (150-180). First, add the calcium ammonia catalyst into purified water, mix ultrasonically at 3°C-8°C to obtain a suspension; then add the modified ZIF-8 into the suspension, stir at a low speed at 3°C-8°C for 30min-40min to load the calcium ammonia catalyst on the modified ZIF-8, centrifuge, take the solid, and dry in vacuo to obtain the catalyst.
[0024] In the preparation method of the above catalyst, in S1: the ultrasonic frequency of ultrasonic mixing is 20kHz~30kHz, and the ultrasonic mixing time is 30min~50min; the rotation speed of centrifugal separation is 4000r / min~6000r / min, and the centrifugal separation time is 15min~25min; the temperature of vacuum drying is 90℃~100℃, and the vacuum drying time is 30min~60min.
[0025] The preparation method of the above catalyst, in S2: the ultrasonic frequency of ultrasonic mixing is 20kHz~30kHz, and the time of ultrasonic mixing is 10min~20min; the rotation speed of low-speed stirring is 60r / min~80r / min, and the time of low-speed stirring is 30min~40min; the rotation speed of centrifugal separation is 4000r / min~6000r / min, and the time is 15min~25min; the temperature of vacuum drying is 90℃~100℃, and the time of vacuum drying is 1h~2h.
[0026] The above-mentioned catalyst for synthesizing polyethylene oxide is used to catalyze the ring-opening polymerization of ethylene oxide to prepare polyethylene oxide, and the amount of the catalyst added is 1.0% to 2.0% of the mass of ethylene oxide. The purity of the polyethylene oxide obtained is above 99.70wt%, and the median molecular weight M med It is between 350,000 and 650,000.
[0027] The catalyst for synthesizing polyethylene oxide and the preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art:
[0028] 1. The present invention uses ZIF-8 (metal organic framework material) to load the calcium ammonia catalyst. The metal organic framework has the characteristics of high porosity, large specific surface area, structural and functional diversity. Its rich pore structure and adjustable chemical properties provide sites and environments for loading calcium ammonia catalysts. By loading the calcium ammonia catalyst onto the metal organic framework, the first aspect is to improve the dispersibility of the calcium ammonia catalyst: the metal organic framework structure can make the calcium ammonia catalyst more evenly dispersed in the polymerization reaction system, increase the contact area between the catalyst and the reactant, improve the reaction efficiency, and thus reduce the amount of calcium ammonia catalyst. Loading a small amount of calcium catalyst can achieve well-controlled polymerization reaction catalysis. On the other hand, the loading can enhance the stability of the calcium ammonia catalyst: the metal organic framework structure can play a certain protective role on the calcium ammonia catalyst, prevent it from agglomerating or deactivating during the reaction, thereby improving the stability and service life of the catalyst, and improving the catalytic stability can make the molecular weight distribution of polyethylene oxide more concentrated, and the molecular weight is easy to control. Thirdly, it has a catalytic synergistic effect: the characteristics of the metal organic framework itself and the catalytic activity of the calcium ammonia catalyst are combined to produce a synergistic effect, further optimizing the selectivity and activity of the reaction and improving the catalytic stability to meet the requirements for the preparation of high-quality and high-stability polyethylene oxide from ethylene oxide.
[0029] 2. In order to improve the loading firmness and stability of ZIF-8 on calcium ammonia catalyst, oligofructose was used to modify ZIF-8, change the pore and surface properties of ZIF-8, and form a thin layer of oligofructose film on the pore and surface of ZIF-8, which can capture calcium ammonia catalyst more quickly, adsorb and load calcium ammonia catalyst more firmly, and is not easy to peel off during the polymerization reaction.
[0030] 3. During the loading of calcium ammonia catalyst, low-speed stirring loading is performed at 3°C to 8°C. Low temperature and low-speed stirring can reduce the solubility of oligofructose membranes, reduce damage to oligofructose membranes, and ensure rapid capture and loading of calcium ammonia catalysts. Low-speed stirring can also reduce damage to the loading structure, making the loaded calcium ammonia catalyst less likely to peel off.
[0031] 4. The design of the loading mass ratio, modified ZIF-8: calcium ammonia catalyst = (25~30): (5~8), can prevent the loading from being overloaded and producing free calcium ammonia catalyst, which will agglomerate in the polymerization reaction system and affect the uniformity and stability of the polymerization reaction, thereby effectively controlling the reaction to produce polyethylene oxide with a more concentrated molecular weight distribution.
[0032] 5. The ZIF-8 used in the present invention is a metal organic framework material ZIF-8 with a high specific surface area, a particle size of more than 650nm, and a specific surface area of more than 1500m² / g, which can well realize the loading and dispersion of the calcium ammonia catalyst.
[0033] 6. The present invention adds methacrylonitrile to the modifier to obtain a relatively more stable calcium ammonia catalyst, which is easier to control the catalytic reaction process, is less likely to produce high molecular weight polyethylene oxide, and makes the molecular weight distribution of polyethylene oxide more concentrated.
[0034] 7. The present invention repeatedly washes the crude calcium ammonia catalyst with a solvent to remove soluble impurities, improve the purity of the calcium ammonia catalyst, and thus reduce the impact of impurities on the polymerization reaction, reduce the generation of polymerization by-product impurities, and thus improve the yield and purity of polyethylene oxide.
[0035] In summary, the catalyst of the present invention has good catalytic stability, the prepared polyethylene oxide has high yield and purity, and the molecular weight distribution is very concentrated, the thermal stability is good, and the quality of low molecular weight polyethylene oxide is greatly improved; the purity of polyethylene oxide is above 99.70wt%, and the median molecular weight M med It is between RMB 350,000 and RMB 650,000 and has good practical value. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0037] Example 1: A catalyst for synthesizing polyethylene oxide, the catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = 28:6.5; the modified ZIF-8 is oligofructose-modified ZIF-8.
[0038] Wherein, the preparation method of calcium ammonia catalyst comprises the following steps:
[0039] S1: Liquid ammonia and metallic calcium with a purity of 99.62% are subjected to complexation reaction at -40°C for 1 hour under the protection of inert gas at a mass ratio of liquid ammonia to metallic calcium = 90:1.2 to generate an ammonia-calcium complex liquid;
[0040] S2: According to the mass ratio, the calcium ammonia complex solution: modifier: solvent = 90:0.5:120, the modifier is dissolved in the solvent, and then added to the calcium ammonia complex solution for modification reaction at -34.5°C for 1.5h, deamination at 5°C for 2.5h, and aging at 140°C for 2.5h to obtain a crude calcium ammonia catalyst;
[0041] The mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = 8:0.8:0.5; the mass ratio of the solvent components is: No. 120 solvent oil: toluene = 9:2;
[0042] S3: The crude calcium ammonia catalyst is resuspended, washed and filtered three times with a solvent, and finally filtered to obtain a solid, which is dried at 125° C. to obtain the calcium ammonia catalyst.
[0043] The above-mentioned method for preparing a catalyst for synthesizing polyethylene oxide comprises the following steps:
[0044] N1: According to the mass ratio, oligofructose: ZIF-8: purified water = 6:55:280, first dissolve oligofructose in purified water, then add ZIF-8, mix at 25kHz ultrasonically for 40min, centrifuge at 5000r / min for 20min, take the solid, vacuum dry at 95℃ for 50min, and obtain modified ZIF-8;
[0045] N2: According to the mass ratio, the calcium ammonia catalyst: modified ZIF-8: purified water = 6.5:28:165. First, add the calcium ammonia catalyst into purified water, and mix ultrasonically at 5°C and 25kHz for 15 minutes to obtain a suspension; then add the modified ZIF-8 into the suspension, and stir at a low speed of 70r / min at 5°C for 50 minutes to load the calcium ammonia catalyst on the modified ZIF-8. Centrifuge at 5000r / min for 20 minutes, take the solid, and dry it in vacuum at 95°C for 1.5 hours to obtain the catalyst.
[0046] Example 2: A catalyst for synthesizing polyethylene oxide, the catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = 25:5.5; the modified ZIF-8 is oligofructose-modified ZIF-8.
[0047] Wherein, the preparation method of calcium ammonia catalyst comprises the following steps:
[0048] S1: Liquid ammonia and metallic calcium with a purity of 99.68% are subjected to complex reaction at -50°C for 1 hour under the protection of inert gas in a mass ratio of 80:1 to generate an ammonia-calcium complex liquid;
[0049] S2: According to the mass ratio, the calcium ammonia complex solution: modifier: solvent = 80:0.3:100, the modifier is dissolved in the solvent, and then added to the calcium ammonia complex solution for modification reaction at -35°C for 1.5h, deamination at -10°C for 2h, and aging at 130°C for 2h to obtain a crude calcium ammonia catalyst;
[0050] The mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = 5:0.5:0.3; the mass ratio of the solvent components is: No. 120 solvent oil: toluene = 8:1.5;
[0051] S3: The crude calcium ammonia catalyst is resuspended, washed and filtered twice with a solvent, and finally filtered to obtain a solid, and dried at 120° C. to obtain the calcium ammonia catalyst.
[0052] The above-mentioned method for preparing a catalyst for synthesizing polyethylene oxide comprises the following steps:
[0053] N1: According to the mass ratio, oligofructose: ZIF-8: purified water = 5.5:50:250, first dissolve oligofructose in purified water, then add ZIF-8, mix at 20kHz ultrasonic for 30min, centrifuge at 4000r / min for 15min, take the solid, vacuum dry at 90℃ for 30min to obtain modified ZIF-8;
[0054] N2: According to the mass ratio, the calcium ammonia catalyst: modified ZIF-8: purified water = 5.5:25:150. First, add the calcium ammonia catalyst into purified water, and mix ultrasonically at 3°C and 20kHz for 10 minutes to obtain a suspension; then add the modified ZIF-8 into the suspension, and stir at a low speed of 3°C and 60r / min for 30 minutes to load the calcium ammonia catalyst on the modified ZIF-8. Centrifuge at 4000r / min for 15 minutes, take the solid, and dry it in vacuum at 90°C for 1 hour to obtain the catalyst.
[0055] Example 3: A catalyst for synthesizing polyethylene oxide, the catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = 30:7.5; the modified ZIF-8 is oligofructose-modified ZIF-8.
[0056] Wherein, the preparation method of calcium ammonia catalyst comprises the following steps:
[0057] S1: Liquid ammonia and metallic calcium with a purity of 99.73% are subjected to complex reaction at -45°C for 1 hour under the protection of inert gas at a mass ratio of 85:1.1 to generate an ammonia-calcium complex liquid;
[0058] S2: According to the mass ratio, the calcium ammonia complex solution: modifier: solvent = 85:0.4:110, the modifier is dissolved in the solvent, and then added to the calcium ammonia complex solution for modification reaction at -34.8°C for 1.5h, deamination at -8°C for 2h, and aging at 135°C for 2h to obtain a crude calcium ammonia catalyst;
[0059] The mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = 6:0.7:0.4; the mass ratio of the solvent components is: No. 120 solvent oil: toluene = 8.5:1.8;
[0060] S3: The crude calcium ammonia catalyst is resuspended, washed and filtered twice with a solvent, and finally filtered to obtain a solid, which is dried at 122° C. to obtain the calcium ammonia catalyst.
[0061] The above-mentioned method for preparing a catalyst for synthesizing polyethylene oxide comprises the following steps:
[0062] N1: According to the mass ratio, oligofructose: ZIF-8: purified water = 5:52:260, first dissolve oligofructose in purified water, then add ZIF-8, mix at 20kHz ultrasonic for 35min, centrifuge at 4500r / min for 18min, take the solid, vacuum dry at 92℃ for 40min to obtain modified ZIF-8;
[0063] N2: According to the mass ratio, the calcium ammonia catalyst: modified ZIF-8: purified water = 7.5:30:160. First, add the calcium ammonia catalyst into purified water, and mix ultrasonically at 4°C and 20kHz for 12 minutes to obtain a suspension; then add the modified ZIF-8 into the suspension, and stir at a low speed of 40 minutes at 65r / min at 4°C to load the calcium ammonia catalyst on the modified ZIF-8. Centrifuge at 4500r / min for 18 minutes, take the solid, and dry it in vacuum at 92°C for 1 hour to obtain the catalyst.
[0064] Example 4: A catalyst for synthesizing polyethylene oxide, the catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = 26:5; the modified ZIF-8 is oligofructose-modified ZIF-8.
[0065] Wherein, the preparation method of calcium ammonia catalyst comprises the following steps:
[0066] S1: Liquid ammonia and metallic calcium with a purity of 99.75% are subjected to complex reaction at -38°C for 1.5h under the protection of inert gas in a mass ratio of 95:1.4 to generate an ammonia-calcium complex liquid;
[0067] S2: According to the mass ratio, the calcium ammonia complex solution: modifier: solvent = 95:0.8:140, the modifier is dissolved in the solvent, and then added to the calcium ammonia complex solution for modification reaction at -34.2°C for 2h, deamination at 15°C for 3h, and aging at 145°C for 3h to obtain a crude calcium ammonia catalyst;
[0068] The mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = 8:0.9:0.5; the mass ratio of the solvent components is: No. 120 solvent oil: toluene = 9:2.5;
[0069] S3: The crude product of calcium ammonia catalyst is resuspended, washed and filtered 4 times with a solvent, and finally filtered to obtain a solid, and dried at 128° C. to obtain a calcium ammonia catalyst.
[0070] The above-mentioned method for preparing a catalyst for synthesizing polyethylene oxide comprises the following steps:
[0071] N1: According to the mass ratio, oligofructose: ZIF-8: purified water = 7:58:285, first dissolve oligofructose in purified water, then add ZIF-8, mix at 30kHz ultrasonically for 45min, centrifuge at 5500r / min for 22min, take the solid, vacuum dry at 98℃ for 55min, and obtain modified ZIF-8;
[0072] N2: According to the mass ratio, the calcium ammonia catalyst: modified ZIF-8: purified water = 5:26:175. First, add the calcium ammonia catalyst into purified water, and mix ultrasonically at 6°C and 30kHz for 18 minutes to obtain a suspension; then add the modified ZIF-8 into the suspension, and stir at a low speed of 75r / min at 6°C for 55 minutes to load the calcium ammonia catalyst on the modified ZIF-8. Centrifuge at 5500r / min for 22 minutes, take the solid, and dry it in vacuum at 98°C for 2 hours to obtain the catalyst.
[0073] Example 5: A catalyst for synthesizing polyethylene oxide, the catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = 27:8; the modified ZIF-8 is oligofructose-modified ZIF-8.
[0074] Wherein, the preparation method of calcium ammonia catalyst comprises the following steps:
[0075] S1: Liquid ammonia and metallic calcium with a purity of 99.64% are subjected to complex reaction at -35°C for 1.5 hours under the protection of inert gas in a mass ratio of 100:1.5 to generate an ammonia-calcium complex liquid;
[0076] S2: The mass ratio of calcium ammonia complex solution: modifier: solvent is 100:1:150. The modifier is dissolved in the solvent and then added to the calcium ammonia complex solution for modification reaction at -34°C for 2h, deamination at 20°C for 3h, and aging at 150°C for 3h to obtain a crude calcium ammonia catalyst;
[0077] The mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = 10:1:0.6; the mass ratio of the solvent components is: No. 120 solvent oil: toluene = 10:3;
[0078] S3: The crude calcium ammonia catalyst is resuspended, washed and filtered 4 times with a solvent, and finally filtered to obtain a solid, which is dried at 130° C. to obtain the calcium ammonia catalyst.
[0079] The above-mentioned method for preparing a catalyst for synthesizing polyethylene oxide comprises the following steps:
[0080] N1: According to the mass ratio, oligofructose: ZIF-8: purified water = 8:60:300, first dissolve oligofructose in purified water, then add ZIF-8, mix by 30kHz ultrasound for 50min, centrifuge at 6000r / min for 25min, take the solid, vacuum dry at 100℃ for 60min to obtain modified ZIF-8;
[0081] N2: According to the mass ratio, calcium ammonia catalyst: modified ZIF-8: purified water = 8:27:180. First, add the calcium ammonia catalyst into purified water, and mix ultrasonically at 8°C and 30kHz for 20 minutes to obtain a suspension; then add the modified ZIF-8 into the suspension, and stir at 8°C and 80r / min for 60 minutes to load the calcium ammonia catalyst on the modified ZIF-8. Centrifuge at 6000r / min for 25 minutes, take the solid, and dry it in vacuum at 100°C for 2 hours to obtain the catalyst.
[0082] Example 6: A catalyst for synthesizing polyethylene oxide, the catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = 25:8; the modified ZIF-8 is oligofructose-modified ZIF-8.
[0083] Wherein, the preparation method of calcium ammonia catalyst comprises the following steps:
[0084] S1: Liquid ammonia and metallic calcium with a purity of 99.55% are subjected to complex reaction at -50°C for 1.5h under the protection of inert gas in a mass ratio of 80:1.5 to generate an ammonia-calcium complex liquid;
[0085] S2: The mass ratio of calcium ammonia complex solution: modifier: solvent is 80:1:100. The modifier is dissolved in the solvent and then added to the calcium ammonia complex solution for modification reaction at -34°C for 1.5h, deamination at 20°C for 2h, and aging at 150°C for 2h to obtain a crude calcium ammonia catalyst;
[0086] The mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = 10:0.5:0.6; the mass ratio of the solvent components is: No. 120 solvent oil: toluene = 8:3;
[0087] S3: The crude calcium ammonia catalyst is resuspended, washed and filtered twice with a solvent, and finally filtered to obtain a solid, which is dried at 130° C. to obtain the calcium ammonia catalyst.
[0088] The above-mentioned method for preparing a catalyst for synthesizing polyethylene oxide comprises the following steps:
[0089] N1: According to the mass ratio, oligofructose: ZIF-8: purified water = 5:60:250, first dissolve oligofructose in purified water, then add ZIF-8, mix by 30kHz ultrasound for 30min, centrifuge at 6000r / min for 15min, take the solid, vacuum dry at 100℃ for 30min, and obtain modified ZIF-8;
[0090] N2: According to the mass ratio, the calcium ammonia catalyst: modified ZIF-8: purified water = 8:25:180. First, add the calcium ammonia catalyst into purified water, and mix ultrasonically at 3°C and 30kHz for 10 minutes to obtain a suspension; then add the modified ZIF-8 into the suspension, and stir at a low speed of 60r / min at 8°C for 60 minutes to load the calcium ammonia catalyst on the modified ZIF-8. Centrifuge at 4000r / min for 25 minutes, take the solid, and dry it in vacuum at 90°C for 2 hours to obtain the catalyst.
[0091] The ZIF-8 used in the above embodiments is a metal organic framework material ZIF-8 with a high specific surface area, a particle size of 70nm to 400nm, and a specific surface area of 1450m² / g, from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0092] Comparative Example 1
[0093] ZIF-8 was not modified with oligofructose; other parameters and methods were the same as in Example 1.
[0094] Comparative Example 2
[0095] In N1, oligofructose:ZIF-8:purified water=2:55:280; other parameters and methods are the same as in Example 1.
[0096] Comparative Example 3
[0097] The catalyst was prepared in N2 at 25°C; other parameters and methods were the same as in Example 1.
[0098] Comparative Example 4
[0099] In N2, calcium ammonia catalyst: modified ZIF-8: purified water = 13:28:165; other parameters and methods are the same as in Example 1.
[0100] Comparative Example 5
[0101] In N2, low-speed stirring was changed to high-speed stirring, with a rotation speed of 150 r / min; other parameters and methods were the same as in Example 1.
[0102] Comparative Example 6
[0103] In S2, methacrylonitrile is not added to the modifier, and the methacrylonitrile component is replaced by ethylene oxide; other parameters and methods are the same as in Example 1.
[0104] Comparative Example 7
[0105] The purification step S3 was omitted, and the crude calcium ammonia catalyst directly replaced the calcium ammonia catalyst; other parameters and methods were the same as those in Example 1.
[0106] The catalysts of the above-mentioned embodiments and comparative examples were respectively used to prepare polyethylene oxide (white powder particles), as follows.
[0107] (1) Low-content catalyst:
[0108] Reactor: Capacity 10L. Material quantity: 1500g n-hexane, 600g ethylene oxide, 6g catalyst. Reaction conditions: argon protection, stirring speed, pressure 0.15MPa, reaction temperature 25℃, reaction time 12h. Post-treatment: filtration, drying.
[0109] (2) High content catalyst:
[0110] Reactor: capacity 10L. Material quantity: 1500g n-hexane, 600g ethylene oxide, 12g catalyst. Reaction conditions: argon protection, stirring speed, pressure 0.15MPa, reaction temperature 25℃, reaction time 12h. Post-treatment: filtration, drying.
[0111] The various polyethylene oxide samples prepared were subjected to the following tests.
[0112] 1. Yield determination:
[0113] 1. Accurately weigh the mass of ethylene oxide before the reaction and the mass of polyethylene oxide obtained after the reaction.
[0114] 2. Calculate the yield using the formula: Yield = (actual mass of polyethylene oxide obtained ÷ theoretical mass of polyethylene oxide obtained) × 100%.
[0115] 2. Purity determination:
[0116] The purity of polyethylene oxide samples was tested by high performance liquid chromatography (HPLC).
[0117] 3. Molecular weight determination:
[0118] Gel permeation chromatography (GPC) was used to detect the molecular weight distribution of polyethylene oxide samples.
[0119] 4. Thermal stability determination:
[0120] The decomposition and softening temperature of polyethylene oxide samples during heating was determined by thermogravimetric analyzer (TGA).
[0121] The test results are shown in Tables 1 and 2 below.
[0122] Table 1 Yield, purity, molecular weight and thermal stability test results of polyethylene oxide in Example
[0123]
[0124] From the results in Table 1, it can be seen that the catalysts of Examples 1 to 6 have good catalytic stability, the prepared polyethylene oxide has high yield and purity, and the molecular weight distribution is very concentrated, the thermal stability is good, and the quality of low molecular weight polyethylene oxide is greatly improved; the purity of polyethylene oxide is above 99.70wt%, and the median molecular weight M med It is between 350,000 and 650,000.
[0125] Table 2 Comparative Example Polyethylene Oxide Yield, Purity, Molecular Weight Thermal Stability Test Results
[0126]
[0127] The results of Table 2 are compared with the results of Example 1: As can be seen from the comparison of the results of Comparative Example 1, oligofructose can play a better loading role in the modification of ZIF-8, the catalyst is evenly distributed and not easy to peel off, and the catalyst after good loading further affects the polymerization reaction, making the molecular weight distribution of polyethylene oxide more concentrated and having better thermal stability. As can be seen from the comparison of the results of Comparative Example 2, reducing the modification amount of oligofructose will affect the loading mass, thereby making the molecular weight distribution of polyethylene oxide wider and reducing thermal stability. As can be seen from the comparison of the results of Comparative Example 3, preparing the catalyst at 25°C will affect the loading mass of the catalyst, and oligofructose is easily soluble in water, affecting the rapid and firm loading of the catalyst, thereby making the molecular weight distribution of polyethylene oxide wider and reducing thermal stability. As can be seen from the comparison of the results of Comparative Example 4, adding an excessive amount of ammonia calcium catalyst will cause the modified ZIF-8 to be overloaded, producing a large amount of free ammonia calcium catalyst, and the free ammonia calcium catalyst is unstable, which will accelerate the polymerization reaction, produce large molecular weight polyethylene oxide, and make the molecular weight distribution of polyethylene oxide wider. By the comparison of comparative example 5 results, it can be seen that in N2, low-speed stirring is changed to high-speed stirring, and the rotating speed is 150r / min, which can destroy the stability of the modified ZIF-8 loaded catalyst, and the catalyst is susceptible to shear force and peeling, and then a certain amount of free catalyst is produced, and the free calcium ammonia catalyst is unstable, which can accelerate the polymerization reaction, produce the polyethylene oxide of large molecular weight, and make the polyethylene oxide molecular weight distribution wider. By the comparison of comparative example 6 results, it can be seen that in S2, methacrylonitrile is not added in the modifier, and the catalytic effect of the calcium ammonia catalyst obtained is relatively unstable, poorly controlled, and can accelerate the polymerization reaction, produce the polyethylene oxide of large molecular weight, and make the polyethylene oxide molecular weight distribution wider. By the comparison of comparative example 7 results, it can be seen that the purification step S3 is omitted, and the calcium ammonia catalyst crude product directly replaces the calcium ammonia catalyst, which can affect the purity of the calcium ammonia catalyst, and impurities can affect the polymerization reaction, produce polymerization byproduct impurities, and then reduce the yield and purity of polyethylene oxide.
Claims
1. A catalyst for synthesizing polyethylene oxide, characterized in that: The catalyst is a modified ZIF-8 loaded with calcium ammonia catalyst, and the loading mass ratio is: modified ZIF-8: calcium ammonia catalyst = (25-30): (5-8); the modified ZIF-8 is oligofructose-modified ZIF-8; The preparation method of the calcium ammonia catalyst comprises the following steps: S1: According to the mass ratio of liquid ammonia:metal calcium = (80-100): (1-1.5), liquid ammonia and metal calcium are subjected to complex reaction under the protection of inert gas to generate ammonia-calcium complex liquid; S2: According to the mass ratio, calcium ammonia complex solution: modifier: solvent = (80-100): (0.3-1): (100-150), dissolving the modifier in the solvent, and then adding the calcium ammonia complex solution to carry out modification reaction, deamination, aging, and obtaining a crude calcium ammonia catalyst; The mass ratio of the modifier components is: ethylene oxide: butyronitrile: methacrylonitrile = (5-10): (0.5-1): (0.3-0.6); the mass ratio of the solvent components is: No. 120 solvent oil: toluene = (8-10): (1.5-3); S3: resuspending, washing and filtering the crude calcium ammonia catalyst with a solvent for 2 to 4 times, and finally filtering, taking out the solid, and drying to obtain the calcium ammonia catalyst; The preparation method of the catalyst comprises the following steps: N1: According to the mass ratio, oligofructose: ZIF-8: purified water = (5-8): (50-60): (250-300), first dissolve oligofructose in purified water, then add ZIF-8, mix by ultrasonication, separate by centrifugation, take the solid, and vacuum dry to obtain modified ZIF-8; N2: According to the mass ratio, calcium ammonia catalyst: modified ZIF-8: purified water = (5-8): (25-30): (150-180). First, add the calcium ammonia catalyst into purified water, mix ultrasonically at 3°C-8°C to obtain a suspension; then add the modified ZIF-8 into the suspension, stir at a low speed of 60r / min-80r / min at 3°C-8°C for 30min-40min to load the calcium ammonia catalyst on the modified ZIF-8, separate by centrifugation, take the solid, and dry in vacuum to obtain the catalyst.
2. A catalyst for synthesizing polyethylene oxide according to claim 1, characterized in that: ZIF-8 is a metal-organic framework material with a high specific surface area. Its particle size is more than 650nm and its specific surface area is more than 1500m² / g.
3. A catalyst for synthesizing polyethylene oxide according to claim 1, characterized in that: In S1, the purity of the metallic calcium is above 99.5%; the temperature of the complex reaction is -50°C to -35°C; and the time of the complex reaction is 1h to 1.5h.
4. A catalyst for synthesizing polyethylene oxide according to claim 1, characterized in that: In S2, the temperature of the modification reaction is -35°C to -34°C, and the time of the modification reaction is 1.5h to 2h; the temperature of the deamination is -10°C to 20°C, and the time of the deamination is 2h to 3h; the temperature of the aging is 130°C to 150°C, and the time of the aging is 2h to 3h.
5. A catalyst for synthesizing polyethylene oxide according to claim 1, characterized in that: In S3, the drying temperature is 120°C or higher.
6. A catalyst for synthesizing polyethylene oxide according to claim 1, characterized in that N1 The ultrasonic frequency of the ultrasonic mixing is 20kHz to 30kHz, and the ultrasonic mixing time is 30min to 50min; the rotation speed of the centrifugal separation is 4000r / min to 6000r / min, and the centrifugal separation time is 15min to 25min; the temperature of the vacuum drying is 90°C to 100°C, and the vacuum drying time is 30min to 60min; In N2: the ultrasonic frequency of the ultrasonic mixing is 20kHz~30kHz, and the time of the ultrasonic mixing is 10min~20min; the rotation speed of the centrifugal separation is 4000r / min~6000r / min, and the time is 15min~25min; the temperature of the vacuum drying is 90℃~100℃, and the time of the vacuum drying is 1h~2h.
7. Use of a catalyst for synthesizing polyethylene oxide, using the catalyst for synthesizing polyethylene oxide according to claim 1, characterized in that: The catalyst is used to catalyze the ring-opening polymerization of ethylene oxide to prepare polyethylene oxide. The amount of catalyst added is 1.0% to 2.0% of the mass of ethylene oxide. The purity of the polyethylene oxide obtained is above 99.70wt%, and the median molecular weight M med It is between 350,000 and 650,000.
Citation Information
Patent Citations
Medium relative molecular mass polyethylene glycol oxide catalyst and preparation thereof
CN101407579A
Supported catalyst for synthesizing low molecular weight polyethylene oxide and preparation and application thereof
CN105504258A